The influences of moisture content variation, number and width of gaps on the withdrawal resistance of self tapping screws inserted in cross laminated timber - Silva, Catarina V. (2016)
A large experimental campaign comprised of 470 withdrawal tests was carried out, aiming to quantify the withdrawal resistance of self-tapping screws (STS) inserted in the side face of cross laminated timber (CLT) elements. In order to deeply understand the “CLT-STS” composite model, the experimental tests considered two main parameters: (i) simple and cyclic changes on moisture content (MC) and (ii) number and width of gaps. Regarding (i), three individual groups of test specimens were stabilized with 8%, 12% and 18% of moisture content and one group was submitted to a six month RH cycle (between 30% and 90% RH). Concerning (ii), different test configurations with 0 (REF), 1, 2 and 3 gaps, and widths equal to 0mm (GAP0) or 4mm (GAP4), were tested. The influences of MC and number of gaps were modeled by means of least square method. Moreover, a revision of a prediction model developed by Uibel and Blaß (2007) was proposed. The main findings of the experimental campaign were: the decrease of withdrawal resistance for specimens tested with MC=18% in most configurations; the unexpected increase of withdrawal resistance as the number of gaps with 0mm increased; and, the surprising increase of withdrawal resistance for REF specimens submitted to the RH cycle.